Recent Publications (Quarterly Journal of Economics, 1945)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 59, Issue 4, August 1945, Pages 642–646, https://doi.org/10.1093/qje/59.4.642 Published: 01 August 1945